Kolaborasi Pemerintah Daerah dan Komunitas Lokal dalam Peningkatan Pelayanan di Wisata Hiu Paus Gorontalo - Mohamad Muflih Hasan; Rusli Isa; Dwi Indah Yuliani Solihin (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
This study examines the collaboration between local government and local communities in improving service quality at the Whale Shark Tourism Destination in Botubarani Village, Bone Bolango Regency, Gorontalo Province. The rapid growth of marine tourism in this area has created economic opportunities for local residents, yet service management and coordination among stakeholders remain a challenge. The study aims to analyze the implementation of collaborative governance in tourism service improvement by focusing on shared commitment, facilitative leadership, face-to-face dialogue, and institutional capacity. A qualitative descriptive approach was applied. Data were collected through direct observation, semi-structured interviews with key stakeholders, and documentation review. The findings reveal that collaboration among stakeholders has been established and has contributed to service delivery, but it is still largely informal and lacks strong institutional arrangements. Facilitative leadership has been demonstrated through coordination and support programs, although capacity-building initiatives are not evenly distributed and not sustained. Face-to-face dialogue exists but is irregular and unstructured, limiting effective communication. Institutional capacity remains constrained by limited human resources, inadequate facilities, and the absence of standardized service procedures. Strengthening formal collaboration mechanisms, improving continuous training, and enhancing institutional capacity are essential to ensure sustainable tourism services and conservation-based destination management.